Recent Advances on Boosting the Cell Voltage of Aqueous Supercapacitors - Gou, Qianzhi; Zhao, Shuang; Wang, Jiacheng; Li, Meng; Xue, Junmin (Nano-Micro Letters, 2020)
Due to its ultra-fast charge/discharge rate, long cyclic life span, and environmental benignity, aqueous supercapacitor (SC) is considered as a proper next-generation energy storage device. Unfortunately, limited by undesirable water electrolysis and unreasonable electrode potential range, aqueous SC normally generates a narrow cell voltage, resulting in a low energy density. To address such challenge, enormous efforts have been made to construct high-voltage aqueous SCs. Despite these achievements, the systematic reviews about this field are still rare. To fill this knowledge gap, this review summarizes the recent advances about boosting the cell voltage of aqueous SCs. From the viewpoint of electrode, doping alkali cations, modulating the electrode mass ratio, and optimizing the surface charge density are regarded as three effective pathways to achieve this goal. However, adjusting the appropriate pH level, introducing redox mediators, and constructing “water-in-salt” electrolyte are other three universal routes from the electrolyte aspect. Furthermore, it is also effective to obtain the high-voltage aqueous SCs through asymmetric design, such as designing asymmetric SCs. The confronting challenges and future development tendency towards the high-voltage aqueous SCs are further discussed. Highlights: 1 High-voltage aqueous supercapacitors hold promise for commercial energy storage devices due to the excellent electrochemical performance. 2 This review summarizes the efficacious measures on boosting the cell voltage of aqueous supercapacitors from the aspects of electrode, electrolyte, and asymmetric design.